Polydatin protects SH-SY5Y in models of Parkinson's disease by promoting Atg5-mediated but parkin-independent autophagy. (March 2020) - Bai, Hua; Ding, Yaqi; Li, Xin; Kong, Deqin; Xin, Chenqi; Yang, Xuekang; Zhang, Chengwu; Rong, Ziqiang; Yao, Chuanhao; Lu, Shenci; Ji, Lei; Li, Lin; et al.
Abstract: Parkinson's disease (PD), the second most common chronic neurodegenerative disorder, broadly remains incurable. Both genetic susceptibility and exposure to deleterious environmental stimuli contribute to dopaminergic neuron degeneration in the substantia nigra. Hence, reagents that can ameliorate the phenotypes rendered by genetic or environmental factors should be considered in PD therapy. In this study, we found that polydatin (Pol ), a natural compound extracted from grapes and red wines, significantly attenuated rotenone- (Rot) or Parkin deficiency-induced mitochondrial dysfunction and cell death in SH-SY5Y, a human dopaminergic neuronal cell line. We showed that Pol significantly attenuated the Rot-induced decrease in cell viability, mitochondrial membrane potential (MMP), and Sirt 1 expression and increase in cell death, reactive oxygen species (ROS) and DJ1 expression. Rot resulted in a decrease in mTOR/Ulk-involved autophagy and an increase in PGC1β/mfn2-involved mitochondrial fusion, which was inhibited by Pol . We further demonstrated that the protective effects of Pol are partially blocked when autophagy-related gene 5 (Atg5) is genetically inactivated, suggesting that Pol-mediated neuroprotection requires Atg5. Moreover, Pol rescued Parkin knockdown-induced oxidative stress, mitochondrial dysfunction, autophagy impairment, and mitochondrial fusion enhancement. Interestingly, Pol treatment could also rescue the mitochondrial morphological abnormality and motorial dysfunction of a Drosophila PD model induced by Parkin deficiency. Thus, Pol could represent a useful therapeutic strategy as a disease-modifier in PD by decreasing oxidative stress and regulating autophagic processes and mitochondrial fusion. Graphical abstract: Schematic diagram underlying the protective effects of polydatin against Parkinson's disease models induced by Rot or Parkin knockdown through recovering redox balance, rescuing autophagy and inhibiting mitochondrial fusion. Image 1 Highlights: Polydatin alleviates oxidative stress and mitochondrial dysfunction in PD models of SH-SY5Y cells. Downregulation of Atg5 blocks the protective effects of polydatin on Rot-induced injury. mTOR-Ulk pathway instead of Parkin might involve in Pol-induced autophagy. Polydatin mitigates dopaminergic, mitochondrial dysfunction and phenotypes in parkin-null flies.